Prevalence of gestational diabetes mellitus among pregnant women attending antenatal care services in Diette Koki memorial hospital, Opolo Bayelsa state, Nigeria - Agofure, Otovwe; Odjimogho, Stella; Okandeji-Barry, Oghenenioborue R. A.; Glasgow, Imomotimi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Gestational diabetes mellitus is a condition in which women without previously diagnosed diabetes exhibit high blood glucose levels during pregnancy. Gestational diabetes which prevalence is on the increase in Nigeria may have negative consequences on the health of the foetus or mother. This study was designed to determine the prevalence of gestational diabetes mellitus and its complications among pregnant women attending antenatal services in Diette Koki memorial hospital Opolo Bayelsa State from 2014-2016. Methods: This was a retrospective study carried out at the Diette Koki Memorial Hospital Opolo in Bayelsa State. The study population comprised pregnant women that attended antenatal care services within the period of January 2014-December 2016. A designed proforma was used to collect the data from the hospital record department. Results: The results of the study showed that the prevalence of gestational diabetes in the year 2014 was 0.023% or 2.33 per 10,000 pregnancies while the prevalence for 2015 was 0.026% or 2.59% per 10000 pregnancies. Furthermore, other complications recorded were hypertension, pre-eclampsia and eclampsia. Similarly, there was a significant correlation between prevalence of gestational diabetes and other complications (r=0.898, p=0.022). Conclusions: In conclusion, prevalence of gestational diabetes was recorded among pregnant women of Diette Koki memorial hospital Opobo Bayelsa State. Therefore, prompt screening and preventive measures should be enforced by health care professionals to prevent maternal and foetal morbidity and mortality.